2020
DOI: 10.9744/jmk.22.1.80-86
|View full text |Cite
|
Sign up to set email alerts
|

Determinant Factors That Influence Entrepreneurial Intention Among Students in Malaysia

Abstract: The unemployment among university students become main issues in Malaysia since the increasing number of umnemployed graduates from higher education institution. In order to minimize this issue, entrepreneurship become one of the main solutions especially for higher education institution in Malaysia. This including the Kolej Islam Antarabangsa Sultan Ismail Petra (KIAS), Kelantan, Malaysia which provided entrepreneurship as main core subjects for their program of studies. Thus, this research tends to examine t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 16 publications
(14 reference statements)
2
6
0
1
Order By: Relevance
“…Entrepreneurship education comprises the skills and characteristics individuals must develop to assist them in making new plans and innovations (Kabir et al, 2017). Students' entrepreneurial characteristics could be developed through entrepreneurship education to create innovative new businesses (Hong et al, 2020). Therefore, entrepreneurship education becomes the independent variable in this study.…”
Section: Entrepreneurship Educationmentioning
confidence: 96%
“…Entrepreneurship education comprises the skills and characteristics individuals must develop to assist them in making new plans and innovations (Kabir et al, 2017). Students' entrepreneurial characteristics could be developed through entrepreneurship education to create innovative new businesses (Hong et al, 2020). Therefore, entrepreneurship education becomes the independent variable in this study.…”
Section: Entrepreneurship Educationmentioning
confidence: 96%
“…Entrepreneurial intention refers to an individual's expressed belief in creating a new business in the future (Botha, Carruthers & Venter, 2019;Hong et al, 2020). It encompasses the willingness to engage in entrepreneurial activities, exhibits entrepreneurial behavior, pursue self-employment, or establish a new business (Nie, 2012).…”
Section: Entrepreneurial Intentionmentioning
confidence: 99%
“…Furthermore, similar research was conducted by [64] and found that Muslim undergraduate students who took entrepreneurship courses at USIU had a good and significant attitude towards entrepreneurial intentions. If students have a positive attitude towards entrepreneurial activities, they are more likely to become entrepreneurs [65]. University graduates are known for their entrepreneurial outlook [66].…”
Section: Attitude and Students' Entrepreneurial Intentionmentioning
confidence: 99%